Worker Reputation and Productivity Incentives - Aron, Debra J. (Journal of Labor Economics, 1987)
This paper examines firms' problem of how to motivate risk-averse workers not to shirk when workers' utility functions are unknown. The problem is studied in a 2-period setting in which a worker's actions today can influence not only his compensation today but the firms' beliefs about his preferences. Firms cannot credibly commit to ignore the revealed information, so workers' actions today affect their future compensation contracts. It is shown that, in the Wilson/Miyazaki equilibrium, firms may pool workers and learn about their types gradually over time rather than inducing them to separate and reveal their types immediately.